2022
DOI: 10.3389/fpls.2022.1062984
|View full text |Cite
|
Sign up to set email alerts
|

Novel sources of drought tolerance in sorghum landraces revealed via the analyses of genotype-by-environment interactions

Abstract: Globally, sorghum is the fifth most important crop, which is used for food, feed and fuel. However, its production and productivity are severely limited by various stresses, including drought. Hence, this study aimed to determine the responses of different drought-tolerance related traits in the Ethiopian sorghum germplasm through multi-environment field trials, thereby identifying novel sources of germplasm that can be used for breeding the crop for drought-tolerance. Three hundred twenty sorghum landraces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…They can be also sources of parental lines for further breeding activities. Our finding confirms that the Ethiopian sorghum landraces often harbored various important traits explained by earlier researchers [2,5,22,24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They can be also sources of parental lines for further breeding activities. Our finding confirms that the Ethiopian sorghum landraces often harbored various important traits explained by earlier researchers [2,5,22,24].…”
Section: Discussionsupporting
confidence: 91%
“…Given its center of origin and diversity [19][20], and tremendous variation in agro-ecologies, Ethiopia is harbored with extremely rich genetic diversity of sorghum landraces [2,16,[21][22], which serves as sources of various important traits. For instance, drought tolerance [16,[23][24], nutritional quality traits [21,[25][26], resistance to grain mold [27] and resistant to ergot and green bug [28]. Ethiopia is also among the top nations that have made significant contributions to the sorghum germplasm collections in the world [29].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable progress has been made in this direction. Studies have shown a positive correlation between chlorophyll content and stay-green characteristics, indicating its role in delaying senescence and maintaining higher yield (Enyew et al 2022). Similarly, researchers have identified several QTLs associated with stay-green, providing valuable targets for breeding programs.…”
Section: Breeding For Tolerance To Abiotic Stresses In Sorghummentioning
confidence: 99%
“…A total of six accessions were better grain yield than Melkam under water-stress regime at Melkassa site. Similarly,Enyew et al (2022) reported that better Ethiopian sorghum accessions that Melkam variety.…”
mentioning
confidence: 91%
“…Only one accession showed better grain yield than the B-35 under water-stress regime. Similarly,(Enyew et al, 2022) reported that landrace accessions that had better mean performance than the improved varieties such as B-35 with respect to grain yield and stay-green which considered as potential novel sources of functional drought tolerance.…”
mentioning
confidence: 97%